Analisis Sistem Tanggung Renteng sebagai Strategi dalam Meminimalisir Risiko Kredit Bermasalah di BUMDesma Bangkit Mandiri Kecamatan Kumpeh Ulu - Jihan Salkiyano; Ahsan Putra Hafiz (Lembaga Yasin AlSys, 2025)
The revolving fund management program through the Badan Usaha Milik Desa Bersama (BUMDESMA) Bangkit Mandiri of Kumpeh Ulu Subdistrict represents a transformation of the PNM Mekaar program, initiated in January 2023, with the aim of strengthening access to capital for underprivileged women engaged in ultra-micro enterprises. One of the key approaches implemented is the joint liability system within the Simpan Pinjam Perempuan (SPP, or Women’s Savings and Loans) groups, yet its effectiveness in addressing non-performing loans remains underexplored. This study aims to analyze the implementation of the joint liability system as a strategy to enhance member solidarity and minimize credit risk. A qualitative descriptive method was used, with data collected through field observation, in-depth interviews with group leaders and members, documentation, and literature review. The findings indicate that the joint liability system is effective in increasing participation, discipline, and member accountability, while also reducing non-performing loans and accelerating group capital turnover. Values of kinship, gotong royong (mutual cooperation), and transparency are embedded in group practices, reinforcing social and economic stability. Nevertheless, challenges persist, particularly low financial literacy and partial non-compliance with repayment obligations. This study underscores that the sustainability of the joint liability system requires intensive mentoring, strengthened group leadership capacity, and adaptive, sustainable institutional management.